Mineral Elements of Seeds, Leaves and Kernel in Sterculia guttata (Kokrus) - R. Katade, Sushama; R. Deshmukh, Madhavi; M. Shah, Sapana; R. Deshpande, Nirmala (Asian Journal of Chemistry, 2016)
Seeds of Sterculia guttata, commonly called ‘Kokrus’ have sedative effect. Metal analysis of seeds, leaves and kernel showed presence of potassium, phosphorus, magnesium, copper, calcium, sodium, zinc, iron and aluminum. Seeds contain stimulating as well as sedative minerals. Seeds showed higher percentage of potassium, phosphorus, magnesium and copper than of other minerals. Copper plays an important role in the production of dopamine (DOPA) and thereby affects the central nervous system. So more consumption of these seeds may lead to sedation.